Maximum Energy for Life: A 21-Day Strategic Plan to Feel Great, Reverse the Aging Process, and Optimize Your Health - Shilstone Mackie (Wiley, 2002)
Thanks to conditioning specialist Mackie Shilstone's innovative, non-traditional training camp, [Roy Jones Jr.] Jones had a remarkably low 6% body fat." (USA Today, March 7, 2003)